Applying metabolomics to cardiometabolic intervention studies and trials: past experiences and a roadmap for the future. - Rankin, N; Preiss, D; Welsh, P; Sattar, N (Oxford University Press, 2016)
Metabolomics and lipidomics are emerging methods for detailed phenotyping of small molecules in samples. It is hoped that such data will i) enhance baseline prediction of patient response to pharmacotherapies (beneficial or adverse)c ii) reveal changes in metabolites shortly after initiation of therapy that may predict patient response, including adverse effects, before routine biomarkers are altered andc iii) give new insights into mechanisms of drug action, particularly where the results of a trial of a new agent were unexpected, and thus help future drug development. In these ways, metabolomics could enhance research findings from intervention studies. This narrative review provides an overview of metabolomics and lipidomics in early clinical intervention studies for investigation of mechanisms of drug action and prediction of drug response (both desired and undesired). We highlight early examples from drug intervention studies associated with cardiometabolic disease. Despite the strengths of such studies, particularly the use of state\of\the\art technologies and advanced statistical methods, currently published studies in the metabolomics arena are largely underpowered and should be considered as hypothesis generating. In order for metabolomics to meaningfully improve stratified medicine approaches to patient treatment there is a need for higher quality studies, with better exploitation of biobanks from randomised clinical trials i.e. with large sample size, adjudicated outcomes, standardised procedures, validation cohorts, comparison to routine biochemistry and both active and control/placebo arms. On the basis of this review, and based on our research experience using clinically established biomarkers, we propose steps to more speedily advance this area of research towards potential clinical impact.